2024
DOI: 10.3390/microorganisms12020263
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Four Pathogenic Oral Bacterial Species in Six Wild Snake Species from Southern Taiwan: Associated Factors

Wen-Hao Lin,
Tein-Shun Tsai,
Po-Chun Chuang

Abstract: The oral cavity of snakes serves as a habitat for various microorganisms, some of which may include potential zoonotic pathogens posing risks to hosts and causing wound infections in snakebite victims. Clinical studies on snakebite cases in Taiwan have identified specific pathogens, such as Enterococcus faecalis (Gram-positive), Morganella morganii, Aeromonas hydrophila, and Pseudomonas aeruginosa (Gram-negative). However, the prevalence of these bacteria in the oral cavity of wild snakes remains largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…In recent years, there have been many reports on the co-infection of humans and animals with M. morganii. For example, M. morganii exists in the oral cavity of snakes and can cause human infection if animals bite or scratch humans [4,5]; Park et al [6] demonstrated that M. morganii strains isolated from captive dolphins pose a risk of fatal zoonotic infection and fail antibiotic treatment due to prolonged resistance; M. morganii is one of the main histamine-producing bacteria, and eating fresh fish and dairy products contaminated with M. morganii can cause food-borne histamine poisoning [7,8]. M. morganii infection can cause cellulitis, endocarditis, osteomyelitis, septic arthritis, diarrhea, and other diseases in humans and animals and even lead to potentially fatal systemic infection [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been many reports on the co-infection of humans and animals with M. morganii. For example, M. morganii exists in the oral cavity of snakes and can cause human infection if animals bite or scratch humans [4,5]; Park et al [6] demonstrated that M. morganii strains isolated from captive dolphins pose a risk of fatal zoonotic infection and fail antibiotic treatment due to prolonged resistance; M. morganii is one of the main histamine-producing bacteria, and eating fresh fish and dairy products contaminated with M. morganii can cause food-borne histamine poisoning [7,8]. M. morganii infection can cause cellulitis, endocarditis, osteomyelitis, septic arthritis, diarrhea, and other diseases in humans and animals and even lead to potentially fatal systemic infection [8][9][10].…”
Section: Introductionmentioning
confidence: 99%